Pregnancies after vaginal radical trachelectomy (RT) in patients with early invasive uterine cervical cancer: results from a single institute - Shota Shinkai; Shinichi Ishioka; Tasuku Mariya; Yuya Fujibe; Miseon Kim; Masayuki Someya; Tsuyoshi Saito (BMC, 2020)
Abstract Background Radical tracheletomy (RT) with pelvic lymphadenectomy has become an option for young patients with early invasive uterine cervical cancer who desire to maintain their fertility. However, this operative method entails a high risk for the following pregnancy due to its radicality. Methods We have performed vaginal RT for 71 patients and have experienced 28 pregnancies in 21 patients. They were followed up carefully according to the follow-up methods we reported previously. Their pregnancy courses and prognoses after the pregnancy were retrospectively reviewed. Results All the vaginal RTs were performed safely without serious complications, including 6 patients who underwent the operation during pregnancy. The median time to be pregnant after RT was 29.5 months. 13 patients (46%) became pregnant without artificial insemination by husband or assisted reproductive technology. Cesarean section was performed for all of them. The median time of pregnancy was 34 weeks, and emergent cesarean section was performed for 7 pregnancies (25%). The median birth weight was 2156 g. Four patients had trouble with cervical cerclage, and they suffered from sudden premature preterm rupture of the membrane (pPROM) during the second trimester of pregnancy. We underwent transabdominal cerclage (TAC) for all of them and careful management for the prevention of uterine infection was performed. One patient had a recurrence of cancer during pregnancy. Conclusions Both the obstetrical prognosis and oncological prognosis after vaginal RT have become favorable for pregnant patients after vaginal RT.